TRACING VARIANTS OF POSSESSIVE IN TETUN - Damianus Talok; Isabel Coryunitha Panis (Universitas Muhammadiyah Makassar, 2026)
Tetun is an Austronesian language spoken by the majority of residents in Belu Regency, Malaka Regency, and several border areas of North Central Timor (TTU) and South Central Timor (TTS) in West Timor, Indonesia, as well as by the majority of the population of Timor-Leste. The language also serves as a lingua franca for non-Tetun speakers residing in Tetun-speaking areas. The urgency of this research lies in the absence of a systematic study documenting and comparing variations in Tetun possessive forms across communities. This study aims to: (1) describe possessive forms in Tetun across three dialect regions—Belu, Malaka, and Wehedan; (2) compare these forms with Tetun Dili (Timor-Leste); (3) identify grammatical possessive constructions applicable across all Tetun-speaking communities; and (4) explain the linguistic and extralinguistic factors influencing such variation. The research employs a qualitative descriptive approach with a distributional method for linguistic analysis. The main findings indicate that West Timorese Tetun exhibits a wider variety of possessive forms than Timorese Tetun, with the Belu dialect (Tetun Terik) serving as the morphological root from which other variants are derived through segmental deletion processes. The novelty of this research lies in the identification of the morphological derivation pattern PRONOUN + -kan as the base form, from which variants arise via two deletion processes: deletion of -ka (producing the -n variant) and deletion of -an (producing the -k variant). Despite significant variation in possessive forms, mutual intelligibility among Tetun speakers from different communities is maintained. The contribution of this study is to provide a grammatical description of Tetun possessives that can serve as a reference in the documentation, revitalization, and teaching of Tetun.